Electrical and structural studies of Polyacrylonitrile (PAN) complexed with inorganic salts / Khairul Bahiyah Md Isa - Md Isa, Khairul Bahiyah (2010)
In the present study, polymer electrolyte films composed of polyacrylonitrile (PAN) as a host polymer, ethylene carbonate (EC) as the plasticizer and lithium triflate (LiCF3SO3) and sodium triflate (NaCF3SO3) as dopant salts were prepared by the solution cast technique. Five systems of polymer electrolytes films have been prepared; these systems are the plasticized-PAN system i.e. PAN-EC system, two salted-PAN systems i.e. PAN-LiCF3SO3 and PAN-NaCF3SO3, and two plasticized-salted PAN systems i.e. PAN-EC-LiCF3SO3 and PAN-EC-NaCF3SO3. The pure PAN film was prepared as a reference. The ionic conductivity for each system is characterized using impedance spectroscopy. The room temperature conductivity of the pure PAN film and the film containing 24 wt.% EC is 1.51 x 10-11 Scm-1 and 3.43 x 10-11 Scm-1 respectively. The room temperature-conductivity for the highest conducting film in the PAN-LiCF3SO3 system and PAN-NaCF3SO3 system is 3.04 x 10-4 S cm-1 and 7.13 x 10- 4 S cm-1 respectively. On addition of plasticizers, the ionic conductivity of these films is further increases to one order of magnitude, i.e. 1.32 x 10-3 S cm-1 and 5.49 x 10-3 S cm- 1 for PAN-EC-LiCF3SO3 film and PAN-EC-NaCF3SO3 film, respectively. The increase in conductivity is due to the increase in number of mobile ions and this can be implied from the dielectric constant, εr - frequency plots. The conductivity-temperature and pressure–dependence studies are then performed on the highest conducting film from the PAN-LiCF3SO3 system, the PAN-NaCF3SO3 system, the PAN-EC-LiCF3SO3 system and the PAN-EC-NaCF3SO3 system. The plots of conductivity versus inverse temperature for all systems followed the Arrhenius rule. The activation energy, Ea values for the PAN+26wt% LiCF3SO3 film, the PAN+24wt%NaCF3SO3 film, the PAN+EC+22wt% LiCF3SO3 film and the PAN+EC+34wt% NaCF3SO3 film have been calculated to be 0.28 eV, 0.23 eV, 0.22 eV and 0.19 eV respectively. It can be observed iii that the film containing NaCF3SO3 salt has higher ionic conductivity and lower activation energy compared to the film containing LiCF3SO3 salt. This result can be explained based on the Lewis acidity of the alkali ions, i.e., the strength of the interaction of cations with the nitrogen atoms from the polymer, PAN. The variations in ionic conductivity in the polymer electrolyte systems with pressure have been carried out at the pressure range between 0.1 atm to 1.0 atm. The conductivity is observed to decrease with increasing pressure for all systems. The activation volume, V* values for the PAN-26wt% LiCF3SO3 film, the PAN-24wt% NaCF3SO3 film, the PAN-EC-22wt% LiCF3SO3 film and the PAN EC-34wt% NaCF3SO3 film have been calculated to be 3.04 x 10-2 cm3 mol-1, 2.86 x 10-2 cm3 mol-1, 1.37 x 10-2 cm3 mol-1 and 1.11 x 10-2 cm3 mol-1, respectively. FTIR spectrum for pure PAN film exhibits the nitrile band, C≡N at 2247 cm-1 and this band shifted to 2244 cm-1 in this complex films. This is due to inductive effect created by the interaction between the nitrogen atom in C≡N with Li+ and Na+ ions from the salts. The XRD studies show the occurrence of complexation between the polymer, the plasticizer and the salts. The SEM micrographs show that the presence of the plasticizer in PAN-salt system helped to obtain regular pore structure, which can increase ion mobility and conductivity. DSC studies show that the pure PAN film has glass transition temperature, Tg at 85.4 °C. The Tg of the film decreases upon addition of the plasticizer and the salts. This result is in good agreement with the conductivity behavior.